2019
DOI: 10.1091/mbc.e18-08-0534
|View full text |Cite
|
Sign up to set email alerts
|

Dual binding motifs underpin the hierarchical association of perilipins1–3 with lipid droplets

Abstract: Lipid droplets (LDs) in all eukaryotic cells are coated with at least one of the perilipin (Plin) family of proteins. They all regulate key intracellular lipases but do so to significantly different extents. Where more than one Plin is expressed in a cell, they associate with LDs in a hierarchical manner. In vivo, this means that lipid flux control in a particular cell or tissue type is heavily influenced by the specific Plins present on its LDs. Despite their early discovery, exactly how Plins target LDs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 64 publications
(94 reference statements)
10
67
0
Order By: Relevance
“…Several AHs were considered so as to cover as much as possible diverse amino acid features. We used an NBD-tagged AH sequence from caveolin 1 (Cav aa159–178, termed Cav1-AH) which was used to target hydrophobic peptides to the surface of cellular LDs (Kassan et al, 2013); a rhodamine-tagged AH sequence from Arfgap1, which is a PL packing sensor (Bigay et al, 2005) also found on LDs (Gannon et al, 2014); a short NBD-tagged AH in the 11-mer repeat sequence of Plin1 (Plin1_108-137; Ajjaji et al, 2019; Rowe et al, 2016), which is the major LD protein in adipocytes (Brasaemle, 2007; Fig. S1 C); and finally, a rhodamine-tagged AH of the nonstructural protein 5 of the hepatitis C virus, which binds to LDs during viral replication (Shi et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several AHs were considered so as to cover as much as possible diverse amino acid features. We used an NBD-tagged AH sequence from caveolin 1 (Cav aa159–178, termed Cav1-AH) which was used to target hydrophobic peptides to the surface of cellular LDs (Kassan et al, 2013); a rhodamine-tagged AH sequence from Arfgap1, which is a PL packing sensor (Bigay et al, 2005) also found on LDs (Gannon et al, 2014); a short NBD-tagged AH in the 11-mer repeat sequence of Plin1 (Plin1_108-137; Ajjaji et al, 2019; Rowe et al, 2016), which is the major LD protein in adipocytes (Brasaemle, 2007; Fig. S1 C); and finally, a rhodamine-tagged AH of the nonstructural protein 5 of the hepatitis C virus, which binds to LDs during viral replication (Shi et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Instead, to reach binding specificity, there might be amphipathic sequences that are well-tuned in hydrophobicity to decrease the neutral lipid/water surface tension enough without binding to bilayers and designed with an optimal interaction with a given neutral lipid. This seems to be at least the case for the most abundant LD proteins, Perilipin 1–5, whose 11-mer repeat AH sequence lacks bulky hydrophobic residues but can specifically detect LD surface (Ajjaji et al, 2019; Brasaemle, 2007; Čopič et al, 2018; Rowe et al, 2016). For instance, Perilipin 3 seems to better bind to LDs in the presence of diacylglycerols (Skinner et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As soon as compression was stopped, surface tension increased again, which is a signature of the desorption of some of the peptides from the surface. This behavior at the TOG interface is unique to LRAT-Nt, as the 11mer repeat domain of Plin1 does not show such response under similar experimental procedures (Ajjaji et al, 2019). With RP, compression led to a continuous decrease of tension (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Recruitment of the peptide to the droplet interface will decrease the interfacial surface tension (Fig. 7A) (Ajjaji et al, 2019; Small, Wang, & Mitsche, 2009), which happened for both RP and TOG (Fig. 7B).…”
Section: Resultsmentioning
confidence: 99%